Development of Teaching Books Based on Science Pop Up To Train Critical Thinking Skills of Elementary Students - Wahyunungsih, Sri; Raharjo, Raharjo; Azizah, Utiya (International Journal for Educational and Vocational Studies, 2020)
This study aims to produce textbooks based on pop up science to train students' critical thinking skills in fifth grade elementary school, to describe the validity, practicality, and effectiveness of pop-up science-based textbooks to practice critical thinking skills on the material "System Digestion in Humans ". This research is a development research that refers to the development model of analysis, design, development, implementation and evaluation (ADDIE). Lesson plan with science-based textbooks pop up are then validated by experts. The results of the validation of the experts stated that the lesson plan with science-based textbooks pop up are valid for used. Furthermore, it was tested on the fifth grade students of Kandangan I / 121 state elementary school at Surabaya with One Group Pretest-Postest Design. The results of a limited scale trial showed that  (1) learning tools with science based pop-up textbooks that are developed in valid categories, (2) lesson plan that are developed practically based on the implementation of lesson plans that are categorized very well and student activities that are relevant to learning, (3) lesson plan which developed are effective based on the results of students' critical thinking skills tests which show that N-Gain 9 students are in the middle category, 6 students are in the high category, and the results of the paired samples t-test with Ho are rejected and the positive response given by the students . It can be concluded that the lesson plans with science-based textbooks pop up are appropriate for training the thinking skills of elementary school students.